Formulation And Antioxidant Activity Testing Of Ethanol Extract Moisturizing Gel From Kesum Leaves (Polygonum Minus Huds.) Using The DPPH (2,2-Diphenyl-1-Picrylhydrazyl) Method - Windy Marcella; Bangkit Riska Permata; Annie Rahmatillah (International Journal of Health Engineering and Technology, 2026)
Free radicals are unstable molecules that can cause cell damage and play a role in premature aging and various skin disorders. One way to inhibit the effects of free radicals is through the use of topical preparations containing antioxidants. Kesum leaves (Polygonum minus Huds) are known to contain bioactive compounds, particularly flavonoids and phenolics, which have the potential to act as natural antioxidants. This study aims to formulate kesum leaf ethanol extract into a moisturizing gel preparation and evaluate its physical quality and antioxidant activity using the DPPH (2,2-diphenyl-1-picrylhydrazyl) method. This study was an experimental study with variations in the concentration of kesum leaf ethanol extract, namely F1 (1%), F2 (2%), and F3 (3%). The evaluation of the physical quality of the gel included organoleptic testing, homogeneity, pH, Viscosity and spreadability. Antioxidant activity was expressed as the IC₅₀ value. The results showed that all gel formulations met the physical quality requirements for preparations. The IC₅₀ values of the gel preparations in F1, F2, and F3 were 169.556 ppm, 150.759 ppm, and 125.396 ppm, respectively, while the positive control showed an IC₅₀ value of 44.792 ppm. An increase in the concentration of kesum leaf ethanol extract in the gel formulation showed a tendency to increase antioxidant activity. Formula F3 had the best antioxidant activity among the gel formulations tested. Thus, kesum leaf ethanol extract has potential as an antioxidant agent.